The Role of Intraoperative Neuromonitoring Modalities in Anterior Cervical Spine Surgery. Issue 1 (February 2023) - Chandra, Akhil Avunoori; Vaishnav, Avani; Shahi, Pratyush; Song, Junho; Mok, Jung; Alluri, R. Kiran; Chen, Darren; Gang, Catherine Himo; Qureshi, Sheeraz
Background: Intraoperative neuromonitoring (IONM) is frequently used during spine surgery to mitigate the risk of neurological injuries. Yet, its role in anterior cervical spine surgery remains controversial. Without consensus on which anterior cervical spine surgeries would benefit the most from IONM, there is a lack of standardized guidelines for its use in such procedures. Purpose : We sought to assess the alerts generated by each IONM modality for 4 commonly performed anterior cervical spinal surgeries: anterior cervical diskectomy and fusion (ACDF), anterior cervical corpectomy and fusion (ACCF), cervical disk replacement (CDR), or anterior diskectomy. In doing so, we sought to determine which IONM modalities (electromyography [EMG], motor evoked potentials [MEP], and somatosensory evoked potentials [SSEP]) are associated with alert status when accounting for procedure characteristics (number of levels, operative level). Methods : We conducted a retrospective review of IONM data collected by Accurate Neuromonitoring, LLC, a company that supports spine surgeries conducted by 400 surgeons in 8 states, in an internally managed database from December 2009 to September 2018. The database was queried for patients who underwent ACCF, ACDF, anterior CDR, or anterior diskectomy in which at least 1 IONM modality was used. The IONM modalities and incidence of alerts were collected for each procedure. The search identified 8854 patients (average age, 50.6 years) who underwent ACCF (n = 209), ACDF (n = 8006), CDR (n = 423), and anterior diskectomy (n = 216) with at least 1 IONM modality. Results : Electromyography was used in 81.3% (n = 7203) of cases, MEP in 64.8% (n = 5735) of cases, and SSEP in 99.9% (n = 8844) of cases. Alerts were seen in 9.3% (n = 671), 0.5% (n = 30), and 2.7% (n = 241) of cases using EMG, MEP and SSEP, respectively. In ACDF, a significant difference was seen in EMG alerts based on the number of spinal levels involved, with 1-level ACDF (6.9%, n = 202) having a lower rate of alerts than 2-level (10.0%, n = 272), 3-level (15.2%, n = 104), and 4-level (23.4%, n = 15). Likewise, 2-level ACDF had a lower rate of alerts than 3-level and 4-level ACDF. A significant difference by operative level was noted in EMG use for single-level ACDF, with C2-C3 having a lower rate of use than other levels. Conclusions : This retrospective review of anterior cervical spinal surgeries performed with at least 1 IONM modality found that SSEP had the highest rate of use across procedure types, whereas MEP had the highest rate of nonuse. Future studies should focus on determining the most useful IONM modalities by procedure type and further explore the benefit of multimodal IONM in spine surgery.